Income inequality in Canada - Sarah Burkinshaw; Yaz Terajima; Carolyn A. Wilkins (Bank of Canada, 2022)
Concerns over rising inequality have heightened in the years following the 2007-09 global financial crisis and, more recently, with the COVID-19 pandemic. This staff discussion paper reviews the historical facts regarding income inequality in Canada, comparing Canada with the United States and reviewing briefly what the literature says about the most likely drivers of the rise in inequality. Data show that income inequality in Canada increased substantially during the 1980s and first half of the 1990s but has been relatively stable over the past 25 years. This increase was felt mainly by low-income earners and younger people, while older people benefited from higher retirement income. Income inequality in the United States has been higher than in Canada for the last four decades, with the main differences observed at the high end of the income distribution. These facts give rise to a number of important questions for future research, including the role (if any) of monetary policy in driving changes in income inequality and that of the monetary policy framework and decisions in reflecting the observed inequality.
Keywords: D31; D63; J31; J32; I24; I32; N32; 330; Central bank research; Monetary and financial indicators; Labour markets